PROMOSI KESENIA, PARIWISATA dan KEBUDAYAAN KABUPATEN BLORA MELALUI FESTIVAL SENI KAMPUNG dan MAJALAH BLORA BERCERITA - Alifa Nur Fitri (Interaksi, 2012)
Blora Regency has a lot of potencies that is not owned by the other regencies, includes its nature, culture, culinary, archeology, geology like old oil mining and also relics of history. They can be a good destination that can invite tourists to visit Blora. Unfortunately, nowadays, there are not many people know the existence of Bumi Samin or Blora. They even know Cepu better, one of sub district in Blora than Blora itself. A lot of potencies like Sate Ayam Blora, Barongan, Tayub dan Fossil Village in Menden, still can not appeal to the tourists to visit Blora. The promotions that have been done by the government of Blora Regency is not good enough to attract them so they still did not realize Blora’s potencies. An activity involving the community in the promotion of tourism  needed, to  raising  awareness and feel pride with them regions  appear. Some have such potential in archeology and geology.  A ble to attract special interest tourists, the potential to attract all walks of society and   near with  people's lives is through artistic and cultural potential of the style of the village which is owned by Blora district. Activities that feature art style village needs to be done to raise public awareness outside the Blora and raising  public awareness of the potential of culture to society Blora. After making theoretical analysis aided by the elected Village Arts Festival event to give the experience of the culture of the village style to the target. In the event of course involves a lot of people with responsibilities and respective jobdesk , Program Manager role is to run the event and ensure fit for purpose. Skills to coordinate, lobbying, negotiation, public speaking, creative, and able to deal with a variety of conditions there were very helpful program manager during the activity.